Designing a Web-Based Health Information System to Improve Data Accuracy and Service Quality at Phana Hospital, Amnat Charoen - Weerapong Thanjangreed; Lloyd Arvin Malaluan (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: This study aimed to design and evaluate a web-based Health Information System to improve data accuracy and service quality at Phana Hospital, Amnat Charoen. Methodology: A research and development design with a mixed-method sequential approach was employed. The system was developed using a structured SDLC framework and implemented over a three-month pilot period. Data accuracy was assessed through medical record audits (n=1,250), usability was measured using the System Usability Scale (n=35 staff), and service quality was evaluated using a modified SERVQUAL questionnaire (n=120 patients). Statistical analysis included paired t-tests to compare pre- and post-implementation outcomes. Main Findings: Incomplete records decreased from 21.0% to 11.8%, duplication errors declined from 10.7% to 4.9%, and average documentation time was reduced from 14.2 to 10.6 minutes (p < 0.001). Service quality improved significantly across all five dimensions, with reliability increasing by +0.67 and responsiveness by +0.69 points. The system achieved a SUS score of 78.4, indicating good usability. Novelty/Originality of this study: This study introduces an integrative framework linking workflow-based system design, embedded real-time validation mechanisms, and service quality performance evaluation within a district-level hospital context, providing a scalable and context-sensitive digital transformation model.